PENGEMBANGAN MATERI AJAR FAMILIE PADA PADLET UNTUK BAHASA JERMAN FASE F - Wardana, Chusnul Diva Pramyta Ade; Wahyuningsih, Fahmi (LATERNE, 2024)
The aim of this research is to understand the development of teaching materials on the topic of ’Familie’ on the Padlet website, using teaching modules from teacher as the data source. This research employs a qualitative approach with a Research and Development (R&D) methodology. Data collection techniques involve inputting the teaching module into the Padlet website. Data analysis techniques use validation from subject matter and media experts, then processed with a Likert scale. The results of this study indicate that Padlet, as a learning medium, is suitable for use in the German language learning process in the classroom, with media expert validation results of 95.556%. Subject matter expert validation results show that 81.81% of the "Familie" teaching materials are suitable for use in German language learning.